Mitigation of Harmonics using Dstatcom with Renewable Energy Sources for Enhanced Power Quality with Intelligent Controller - Sravani, G.; Rajesh, A. (International Journal of Engineering and Technology, 2018)
In this paper, distributed static compensator (DSTATCOM) is used to mitigate of the harmonics show in the source streams on account of non-linear and unbalanced burdens. Here a Photovoltaic (PV cell) based inverter is used as a parallel active filter for the balance of the present harmonics. A unit vector control hypothesis is used to deliver 3-á¶² (three phase) reference source streams. Hysteresis current controller is utilized for restricting the changing recurrence and to deliver characterized harmonics. In this paper, a correlation of total harmonic distortion of an appropriated system is completed with and without DSTATCOM. A fuzzy logic controller is acquainted into the system with enhance the power quality of the dispersed system. The whole procedure was done on MATLAB/SIMULINK to acquire the coveted outcomes.Â